Manufacturing method of solid-state battery

The method for manufacturing solid-state batteries with a thermally expandable resin layer and metal casing addresses electrode cracking by restoring conductivity, enhancing battery capacity retention.

JP7600690B2Active Publication Date: 2024-12-17TOYOTA JIDOSHA KK
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021001436
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-07
Publication Date
2024-12-17
Estimated Expiration
2041-01-07

AI Technical Summary

Technical Problem

Solid-state batteries face capacity reduction due to electrode cracking caused by expansion and contraction during charging, which conventional methods fail to effectively address by merely coating with resins of different elastic moduli.

Method used

A manufacturing method involving a laminate structure with a thermally expandable resin layer covering the electrodes, housed in a metal casing, where the battery is discharged to SOC 0% and subjected to a specified temperature, allowing the expandable resin to fill cracks and restore conductivity.

Benefits of technology

This method effectively suppresses capacity reduction by restoring the conductive path in electrodes, achieving high charge/discharge efficiency and maintaining battery capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600690000002
    Figure 0007600690000002
  • Figure 0007600690000003
    Figure 0007600690000003
  • Figure 0007600690000004
    Figure 0007600690000004
Patent Text Reader

Abstract

To provide a method for manufacturing a solid state battery capable of suppressing decrease in capacity caused by electrode cracking.SOLUTION: A solid state battery includes: laminate in which a positive electrode, a solid state electrolyte layer, and a negative electrode are laminated in order; a thermal expansion resin layer for covering at least part of the laminate; and a metal housing for housing the laminate and the thermal expansion resin layer. A method for manufacturing the solid state battery includes the steps of: discharging the solid state battery up to SOC 0%; and applying predetermined temperature to the discharged solid state battery. The thermal expansion resin layer and the metal housing are in contact with each other.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for manufacturing a solid-state battery. [Background technology]

[0002] In recent years, with the rapid spread of information-related devices and communication devices such as personal computers, video cameras, and mobile phones, the development of batteries to be used as power sources for these devices has become important. In the automobile industry, too, development of high-output, high-capacity batteries for electric vehicles or hybrid vehicles is underway. Moreover, solid-state batteries have attracted attention because they use a solid electrolyte as the electrolyte between the positive electrode and the negative electrode, instead of an electrolytic solution containing an organic solvent.

[0003] Patent Document 1 discloses that the resin layer on the side surface of the all-solid-state battery has a multilayer structure having a first resin layer and a second resin layer in this order from the side closer to the side surface of the all-solid-state battery laminate, and that the elastic modulus of the first resin layer is smaller than the elastic modulus of the second resin layer.

[0004] Patent Document 2 discloses a method for inspecting an all-solid-state battery based on the amount of voltage drop due to self-discharge.

[0005] Patent Document 3 discloses that a passivation layer is provided on the end face of the laminate of the all-solid-state battery, and that the passivation layer contains LiI hydrate.

[0006] Patent Document 4 discloses a capacity recovery method for an all-solid-state battery, which includes producing a second all-solid-state battery by applying pressure to a first all-solid-state battery by an isostatic pressing method, and is characterized in that the first all-solid-state battery has been charged and discharged at least once. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2019-153535 A [Patent Document 2] JP 2015-122169 A [Patent Document 3] JP 2020-155301 A [Patent Document 4] JP 2020-068170 A Summary of the Invention [Problem to be solved by the invention]

[0008] In solid-state batteries, there is a risk of the capacity decreasing due to electrode cracking.

[0009] The present disclosure has been made in consideration of the above-mentioned circumstances, and has as its main object to provide a manufacturing method for a solid-state battery that can suppress capacity reduction due to electrode cracking. [Means for solving the problem]

[0010] A method for producing a solid-state battery according to the present disclosure is a method for producing a solid-state battery including a laminate in which a positive electrode, a solid electrolyte layer, and a negative electrode are laminated in this order, a thermally expandable resin layer that covers at least a portion of the laminate, and a metal case that houses the laminate and the thermally expandable resin layer, Discharging the solid-state battery to 0% SOC; and applying a predetermined temperature to the discharged solid-state battery; The thermally expandable resin layer is in contact with the metal housing. Effect of the Invention

[0011] The present disclosure can provide a method for manufacturing a solid-state battery that can suppress a decrease in capacity due to electrode cracking. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a schematic cross-sectional view in a planar direction showing an example of a solid-state battery according to the present disclosure. [Diagram 2] FIG. 2 is a flow chart showing an example of the manufacturing method of the present disclosure. [Diagram 3] FIG. 3 is a schematic diagram illustrating the capacity recovery mechanism of a solid-state battery obtained by the production method of the present disclosure. [Figure 4] FIG. 4 is a schematic diagram of the solid-state battery of Example 1 (laminate-PVDC resin layer-SUS case). [Diagram 5] FIG. 5 is a schematic diagram of the solid-state battery of Comparative Example 1 (laminate-tape-SUS case). [Figure 6] FIG. 6 is a schematic diagram of the solid-state battery of Comparative Example 2 (laminate-epoxy resin-acrylic resin-space-SUS case). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] A method for producing a solid-state battery according to the present disclosure is a method for producing a solid-state battery including a laminate in which a positive electrode, a solid electrolyte layer, and a negative electrode are laminated in this order, a thermally expandable resin layer that covers at least a portion of the laminate, and a metal case that houses the laminate and the thermally expandable resin layer, Discharging the solid-state battery to 0% SOC; and applying a predetermined temperature to the discharged solid-state battery; The thermally expandable resin layer is in contact with the metal housing.

[0014] In the present disclosure, SOC (State of Charge) indicates the ratio of the charge capacity to the fully charged capacity of a battery, with the fully charged capacity being SOC 100%. The SOC may be estimated from, for example, the open circuit voltage (OCV) of a solid-state battery.

[0015] A degradation mode specific to solid-state batteries is electrode cracking caused by the expansion and contraction of the electrodes during repeated charging. The capacity degradation caused by this phenomenon will not recover unless the cracked area is re-established as conductive. In conventional technology, cracks are suppressed by covering the periphery with a resin with a different elastic modulus, but this does not mean that cracks will not occur, and once a crack has occurred, it is difficult to make it conductive again. In the present disclosure, the coating material of the electrode body is limited to a resin with a high linear expansion coefficient (thermal expansion resin), the resin-coated electrode body is housed in a metal case, and a specified temperature load is applied to the solid-state battery in a discharged state as a capacity recovery process. As a result, cracks and voids generated in the electrode body are filled by the expansion pressure of the thermal expansion resin covering the periphery of the electrode body, and the conductive path is restored. At that time, in order to efficiently apply pressure to the electrode body as a battery configuration, the outside of the resin is made into a strong metal case, and further, highly effective capacity recovery is realized by the temperature load process in a discharged state where cracks are significantly generated, and the capacity decrease due to electrode cracks can be suppressed.

[0016] FIG. 1 is a schematic cross-sectional view in a planar direction showing an example of a solid-state battery according to the present disclosure. As shown in Fig. 1, the solid-state battery has a laminate having a positive electrode terminal and a negative electrode terminal, and a thermally expandable resin layer covering at least a part of the laminate, and the laminate and the thermally expandable resin layer are contained in a metal case, and the thermally expandable resin layer and the metal case are in contact with each other. Note that the surface direction means a direction perpendicular to the stacking direction.

[0017] FIG. 2 is a flow chart showing an example of the manufacturing method of the present disclosure. As shown in Figure 2, first, the solid-state battery is discharged to SOC 0%, and then the specified temperature is applied to the solid-state battery. This makes it possible to suppress the capacity loss caused by electrode cracking, and to obtain a solid-state battery with high charge / discharge efficiency.

[0018] FIG. 3 is a schematic diagram illustrating the capacity recovery mechanism of a solid-state battery obtained by the production method of the present disclosure. As shown in Figure 3, discharging a solid-state battery to 0% SOC cuts off the conductive path and reduces the capacity of the solid-state battery. By then exposing the solid-state battery to a specified temperature, the expansion pressure of the thermal expansion resin from outside the electrode body restores the conductive path, recovering the capacity of the solid-state battery and suppressing the capacity reduction due to electrode cracking.

[0019] The method for producing a solid-state battery according to the present disclosure includes (1) a discharging step, and (2) a specified temperature applying step.

[0020] (1)Discharge process The discharging step is a step of discharging the solid-state battery to an SOC of 0%. The discharge process maximizes the amount of voids in the electrodes caused by electrode cracking in solid-state batteries. Before the discharging step, a solid-state battery (first solid-state battery) is prepared, which includes a laminate in which a positive electrode, a solid electrolyte layer, and a negative electrode are laminated in this order, a thermally expandable resin layer covering at least a portion of the laminate, and a metal casing that contains the laminate and the thermally expandable resin layer, with the thermally expandable resin layer in contact with the metal casing.

[0021] (2) Specified temperature application process The specified temperature application step is a step of applying a specified temperature to the discharged solid-state battery. The specified temperature application process eliminates the gaps in the electrodes caused by electrode cracks due to the expansion pressure of the thermal expansion resin. A solid-state battery (second solid-state battery) with restored capacity can be obtained by applying the specified temperature. The requirement for the specified temperature may be the maximum temperature that is equal to or lower than the heat resistance temperature of the battery constituent materials and does not cause significant deterioration of the battery. One way to determine the temperature at which battery degradation does not decrease significantly is, for example, to conduct a durability test at different temperatures and determine the boundary temperature at which the slope of the Arrhenius plot changes (the inflection point temperature of the Arrhenius plot).

[0022] The solid-state battery of the present disclosure includes a laminate in which a positive electrode, a solid electrolyte layer, and a negative electrode are laminated in this order, a thermally expandable resin layer covering at least a portion of the laminate, and a metal casing that contains the laminate and the thermally expandable resin layer, and the thermally expandable resin layer is in contact with the metal casing. In the present disclosure, the solid-state battery before the discharging step may be referred to as a first solid-state battery, and the solid-state battery after the specified temperature application step may be referred to as a second solid-state battery. However, since the first solid-state battery and the second solid-state battery have the same configuration, the first solid-state battery and the second solid-state battery are collectively referred to as solid-state batteries.

[0023] [Thermal expansion resin layer] The thermally expandable resin layer needs only to cover at least a portion of the laminate and to be in contact with the metal housing. The thermally expandable resin layer needs only to cover at least a part of the laminate, and may cover the side surfaces of the laminate. The thermally expandable resin layer includes a thermally expandable resin. As the thermal expansion resin, for example, acrylic resin (linear expansion coefficient: 7×10 -5 / ℃), epoxy resin (linear expansion coefficient: 3×10 -5 / ℃), polyvinylidene chloride (PVDC) (linear expansion coefficient: 19×10 -5 / ℃) etc. Assuming there is no deformation of the metal casing, when the thermally expandable resin layer is 5 mm thick and the temperature is raised from 20°C to 120°C, the acrylic resin will expand to a thickness of 35 μm, the epoxy resin to a thickness of 15 μm, and the PVDC to a thickness of 95 μm.

[0024] [Metal case] The metal housing only needs to accommodate the laminate and the thermally expandable resin layer and be in contact with the thermally expandable resin layer. The metal housing may be, for example, a stainless steel housing.

[0025] [Laminate] The laminate is formed by laminating a positive electrode, a solid electrolyte layer, and a negative electrode in this order.

[0026] [Positive electrode] The positive electrode includes a positive electrode layer and a positive electrode current collector. A positive electrode terminal may be connected to the positive electrode, and the positive electrode current collector may be the positive electrode terminal.

[0027] [Positive electrode layer] The positive electrode layer contains a positive electrode active material, and may contain optional components such as a solid electrolyte, a conductive material, and a binder.

[0028] There is no particular limitation on the type of positive electrode active material, and any material that can be used as an active material for a battery can be used. When the battery is a lithium secondary battery, the positive electrode active material can be, for example, metallic lithium (Li), a lithium alloy, LiCoO2, LiNi 0.8 Co 0.15Al 0.05 O2, LiNi x Co 1-x O2(0 <x<1)、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 Examples of the Li-Mn spinel substituted with a different element include LiO2, LiMnO2, Li-Mn spinel substituted with a different element, lithium titanate, lithium metal phosphate, LiCoN, Li2SiO3, and Li4SiO4, transition metal oxides, TiS2, Si, SiO2, Si alloys, and lithium-storing intermetallic compounds. The Li-Mn spinel substituted with a different element is, for example, LiMn 1.5 Ni 0.5 O4, LiMn 1.5 Al 0.5 O4, LiMn 1.5 Mg 0.5 O4, LiMn 1.5 Co 0.5 O4, LiMn 1.5 Fe 0.5 O4 and LiMn 1.5 Zinc 0.5 O4, etc. Lithium titanate is, for example, Li4Ti5O 12 The lithium metal phosphates are, for example, LiFePO4, LiMnPO4, LiCoPO4, and LiNiPO4. The transition metal oxides are, for example, V2O5, and MoO3. The lithium storage intermetallic compounds are, for example, Mg2Sn, Mg2Ge, Mg2Sb, and Cu3Sb. Examples of lithium alloys include Li-Au, Li-Mg, Li-Sn, Li-Si, Li-Al, Li-B, Li-C, Li-Ca, Li-Ga, Li-Ge, Li-As, Li-Se, Li-Ru, Li-Rh, Li-Pd, Li-Ag, Li-Cd, Li-In, Li-Sb, Li-Ir, Li-Pt, Li-Hg, Li-Pb, Li-Bi, Li-Zn, Li-Tl, Li-Te, and Li-At. Examples of Si alloys include alloys with metals such as Li, and may also be alloys with at least one metal selected from the group consisting of Sn, Ge, and Al. The shape of the positive electrode active material is not particularly limited, but may be particulate. When the positive electrode active material is particulate, the positive electrode active material may be primary particles or secondary particles. The average particle diameter (D50) of the positive electrode active material may be, for example, 1 nm or more and 100 μm or less, or 10 nm or more and 30 μm or less. A coating layer containing a Li-ion conductive oxide may be formed on the surface of the positive electrode active material, because this can suppress the reaction between the positive electrode active material and the solid electrolyte. Examples of Li-ion conductive oxides include LiNbO3 and Li4Ti5O 12 , and Li3PO4. The thickness of the coating layer is, for example, 0.1 nm or more, and may be 1 nm or more. Meanwhile, the thickness of the coating layer is, for example, 100 nm or less, and may be 20 nm or less. The coverage of the coating layer on the surface of the positive electrode active material is, for example, 70% or more, and may be 90% or more.

[0029] As the solid electrolyte, the same ones as those exemplified in the solid electrolyte layer can be exemplified. The content of the solid electrolyte in the positive electrode layer is not particularly limited, but may be, for example, within a range of 1 mass % to 80 mass % when the total mass of the positive electrode layer is taken as 100 mass %.

[0030] The conductive material may be a known material, such as a carbon material and metal particles. The carbon material may be at least one selected from the group consisting of acetylene black, furnace black, VGCF, carbon nanotubes, and carbon nanofibers. In particular, from the viewpoint of electronic conductivity, at least one selected from the group consisting of VGCF, carbon nanotubes, and carbon nanofibers may be used. The metal particles may be particles of Ni, Cu, Fe, SUS, etc. The content of the conductive material in the positive electrode layer is not particularly limited.

[0031] Examples of the binder include acrylonitrile butadiene rubber (ABR), butadiene rubber (BR), polyvinylidene fluoride (PVdF), styrene butadiene rubber (SBR), etc. The content of the binder in the positive electrode layer is not particularly limited.

[0032] The thickness of the positive electrode layer is not particularly limited.

[0033] The positive electrode layer can be formed by a conventionally known method. For example, a positive electrode active material and, if necessary, other components are put into a solvent and stirred to prepare a positive electrode layer slurry, and the positive electrode layer slurry is applied onto one side of a support such as a positive electrode current collector and dried to obtain a positive electrode layer. Examples of the solvent include butyl acetate, butyl butyrate, heptane, and N-methyl-2-pyrrolidone (NMP). The method for applying the positive electrode layer slurry onto one surface of a support such as a positive electrode current collector is not particularly limited, and examples thereof include a doctor blade method, a metal mask printing method, an electrostatic application method, a dip coating method, a spray coating method, a roll coating method, a gravure coating method, and a screen printing method. The support can be appropriately selected from those having self-supporting properties and is not particularly limited. For example, metal foils such as Cu and Al can be used.

[0034] As another method for forming the positive electrode layer, the positive electrode layer may be formed by pressure molding a powder of a positive electrode mixture containing a positive electrode active material and other components as necessary. When the powder of the positive electrode mixture is pressure molded, a press pressure of about 1 MPa to 600 MPa is usually applied. The method of applying pressure is not particularly limited, but examples thereof include a method of applying pressure using a plate press, a roll press, or the like.

[0035] [Positive electrode current collector] The positive electrode current collector may be a known metal that can be used as a current collector for a battery. Examples of such metals include metal materials containing one or more elements selected from the group consisting of Cu, Ni, Al, V, Au, Pt, Mg, Fe, Ti, Co, Cr, Zn, Ge, and In. Examples of the positive electrode current collector include SUS, aluminum, nickel, iron, titanium, and carbon. The shape of the positive electrode current collector is not particularly limited, and may be in various shapes such as a foil shape, a mesh shape, etc. The thickness of the positive electrode current collector varies depending on the shape, but may be, for example, in the range of 1 μm to 50 μm, or in the range of 5 μm to 20 μm. The positive electrode current collector may be connected to a positive electrode terminal, or the positive electrode current collector may be the positive electrode terminal.

[0036] [Negative electrode] The negative electrode includes a negative electrode current collector and a negative electrode layer. A negative electrode terminal may be connected to the negative electrode, and the negative electrode current collector may be the negative electrode terminal.

[0037] [Negative electrode layer] The negative electrode layer contains at least a negative electrode active material, and optionally contains a conductive material, a binder, a solid electrolyte, and the like. The negative electrode active materials include graphite, mesocarbon microbeads (MCMB), highly oriented graphite (HOPG), hard carbon, soft carbon, lithium alone, lithium alloy, Si alone, Si alloy, and Li4Ti5O 12 As the lithium alloy and the Si alloy, the same ones as those exemplified in the positive electrode active material can be used. The shape of the negative electrode active material is not particularly limited, and may be particulate, plate-like, etc. When the negative electrode active material is particulate, the negative electrode active material may be primary particles or secondary particles. The average particle diameter (D50) of the negative electrode active material may be, for example, 1 nm or more and 100 μm or less, or 10 nm or more and 30 μm or less. The shape of the negative electrode active material is not particularly limited, and examples thereof include a particulate shape and a plate shape. The conductive material and binder used in the negative electrode layer may be the same as those exemplified in the positive electrode layer, and the solid electrolyte used in the negative electrode layer may be the same as those exemplified in the solid electrolyte layer. The thickness of the negative electrode layer is not particularly limited, but may be, for example, 10 to 100 μm. The content of the negative electrode active material in the negative electrode layer is not particularly limited, and may be, for example, 20% by mass to 90% by mass.

[0038] [Negative electrode current collector] The material of the negative electrode current collector may be a material that does not alloy with Li, and examples of such materials include SUS, Cu, and Ni. Examples of the shape of the negative electrode current collector include foil and plate. The planar shape of the negative electrode current collector is not particularly limited, and examples of such shapes include a circle, an ellipse, a rectangle, and any polygon. The thickness of the negative electrode current collector varies depending on the shape, and may be, for example, within a range of 1 μm to 50 μm, or within a range of 5 μm to 20 μm. The negative electrode current collector may be connected to a negative electrode terminal, or the negative electrode current collector may be the negative electrode terminal.

[0039] [Solid electrolyte layer] The solid electrolyte layer includes at least a solid electrolyte. As the solid electrolyte contained in the solid electrolyte layer, any known solid electrolyte that can be used in solid-state batteries can be appropriately used, and examples of such solid electrolyte include oxide-based solid electrolytes and sulfide-based solid electrolytes. Examples of sulfide-based solid electrolytes include Li2S-P2S5, Li2S-SiS2, LiX-Li2S-SiS2, LiX-Li2S-P2S5, LiX-Li2O-Li2S-P2S5, LiX-Li2S-P2O5, LiX-Li3PO4-P2S5, and Li3PS4. The above description of "Li2S-P2S5" means a material made using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions. In addition, "X" in the above LiX indicates a halogen element. The raw material composition containing LiX may contain one type or two or more types of LiX. When two or more types of LiX are contained, the mixing ratio of the two or more types is not particularly limited. The molar ratio of each element in the sulfide-based solid electrolyte can be controlled by adjusting the content of each element in the raw material. The molar ratio and composition of each element in the sulfide-based solid electrolyte can be measured, for example, by ICP emission spectrometry.

[0040] The sulfide-based solid electrolyte may be a sulfide glass, a crystallized sulfide glass (glass ceramics), or a crystalline material obtained by subjecting a raw material composition to a solid-phase reaction treatment. The crystalline state of the sulfide-based solid electrolyte can be confirmed, for example, by subjecting the sulfide-based solid electrolyte to powder X-ray diffraction measurement using CuKα radiation.

[0041] The sulfide glass can be obtained by subjecting a raw material composition (e.g., a mixture of Li2S and P2S5) to an amorphous process, such as mechanical milling.

[0042] Glass ceramics can be obtained, for example, by heat treating a sulfide glass. The heat treatment temperature may be any temperature higher than the crystallization temperature (Tc) of the sulfide glass observed by thermal analysis, and is usually 195° C. or higher. On the other hand, there is no particular upper limit to the heat treatment temperature. The crystallization temperature (Tc) of the sulfide glass can be measured by differential thermal analysis (DTA). The heat treatment time is not particularly limited as long as the desired crystallinity of the glass ceramic is obtained, but is, for example, within the range of 1 minute to 24 hours, and particularly within the range of 1 minute to 10 hours. The method of heat treatment is not particularly limited, but may be, for example, a method using a baking furnace.

[0043] Examples of oxide-based solid electrolytes include substances having a garnet-type crystal structure containing, for example, Li, La, A (A is at least one of Zr, Nb, Ta, and Al), and O. 3+x PO 4-x N x (1≦x≦3), etc.

[0044] The solid electrolyte may be in the form of particles from the viewpoint of ease of handling. Furthermore, the average particle size (D50) of the solid electrolyte particles is not particularly limited, but the lower limit may be 0.5 μm or more and the upper limit may be 2 μm or less.

[0045] In this disclosure, the average particle size of particles is the volume-based median diameter (D50) value measured by laser diffraction / scattering particle size distribution measurement, unless otherwise specified. In this disclosure, the median diameter (D50) is the diameter (volume average diameter) at which the cumulative volume of particles is half (50%) of the total volume when the particles are arranged in order from the smallest particle size.

[0046] The solid electrolyte may be used alone or in combination of two or more kinds. When two or more kinds of solid electrolytes are used, the two or more kinds of solid electrolytes may be mixed, or two or more layers of the solid electrolyte may be formed to form a multilayer structure. The proportion of the solid electrolyte in the solid electrolyte layer is not particularly limited, but is, for example, 50% by mass or more, and may be in the range of 60% by mass or more and 100% by mass or less, 70% by mass or more and 100% by mass or less, or may be 100% by mass.

[0047] The solid electrolyte layer may contain a binder from the viewpoint of expressing plasticity, etc. Examples of such binders include the materials exemplified as the binders used in the positive electrode layer. However, in order to facilitate high output, the binder may be contained in the solid electrolyte layer in an amount of 5 mass % or less from the viewpoint of preventing excessive aggregation of the solid electrolyte and enabling the formation of a solid electrolyte layer having a uniformly dispersed solid electrolyte.

[0048] The method for forming the solid electrolyte layer includes a method of pressing a powder of a solid electrolyte material containing a solid electrolyte, etc. When pressing the powder of the solid electrolyte material, a press pressure of about 1 MPa or more and 600 MPa or less is usually applied. The method of applying pressure is not particularly limited, but may be any of the pressure applying methods exemplified in the formation of the positive electrode layer.

[0049] The thickness of the solid electrolyte layer is not particularly limited, and is usually 0.1 μm or more and 1 mm or less.

[0050] The solid-state battery may be a primary battery or a secondary battery, but may be a secondary battery. The secondary battery can be repeatedly charged and discharged. The secondary battery is useful, for example, as an in-vehicle battery. The solid-state battery may be a solid-state lithium secondary battery. EXAMPLES

[0051] Example 1 A laminate was prepared by laminating a positive electrode current collector foil, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, and a negative electrode current collector foil in this order. The structure of the laminate is as follows: Positive electrode current collector foil: Aluminum, thickness t = 15 μm ·Positive electrode layer: NCM(LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2: Positive electrode active material) / Solid electrolyte / PVdF (binder) = 80:15:5wt% Negative electrode layer: Si (negative electrode active material) / solid electrolyte / SBR (binder) = 50:48:2wt% Negative electrode current collector foil: Cu thickness t = 15 μm ·Solid electrolyte layer: sulfide solid electrolyte The solid-state battery was obtained by the following method. The laminate was coated with polyvinylidene chloride (PVDC) resin (thickness 5 mm) and solidified to form a thermally expandable resin layer on the side of the laminate. The laminate and the thermally expandable resin layer were inserted into a SUS case as a metal case so that the thermally expandable resin layer was in contact with the SUS case to form a solid-state battery. FIG. 4 is a schematic diagram of the solid-state battery of Example 1 (laminate-PVDC resin layer-SUS case).

[0052] [Evaluation method] The solid-state battery of Example 1 was subjected to the following durability test to measure the capacity retention rate. The results are shown in Table 1.

[0053] [Discharge capacity measurement before durability test] The solid-state battery obtained in Example 1 was charged in an unconstrained state at 25° C. and 0.1 C from SOC 0% to 100%, and discharged at 0.1 C from SOC 100% to 0%, and the discharge capacity of the solid-state battery before the durability test was measured. [Durability test] The solid-state battery obtained in Example 1 was charged and discharged at 25° C. for a total of 100 cycles, with one cycle being charging from 0% to 100% SOC at 1C and discharging from 100% to 0% SOC at 1C. [Discharge capacity measurement after durability test] The solid-state battery obtained in Example 1 after the durability test was charged at 25° C. and 0.1 C from SOC 0% to 100%, and discharged at 0.1 C from SOC 100% to 0%, and the discharge capacity of the solid-state battery after the durability test was measured. The capacity retention rate of the solid-state battery was calculated by dividing the discharge capacity of the solid-state battery after the durability test by the discharge capacity before the durability test, and multiplying the result by 100. Table 1 shows the results showing the capacity retention rate immediately after the cycle test of Example 1, when the capacity retention rate immediately after the cycle test of Comparative Example 1 described later is set to 100%. [Discharge process] After calculating the capacity retention rate, the SOC of the solid-state battery was adjusted to 0% as a discharging process. [Specified temperature application process] Thereafter, as a specified temperature application step, the solid-state battery was exposed to an environment of 130°C set as an excessive temperature for 30 minutes, and the capacity retention rate was measured again. In addition, as a specified temperature application step, the solid-state battery was exposed to an environment of 120°C set as an appropriate temperature for 30 minutes, and the capacity retention rate was measured again. Table 1 shows the results of the capacity retention rate after application of an excessive temperature in Example 1 when the capacity retention rate immediately after the cycle test in Comparative Example 1 described later is set to 100%, and the capacity retention rate after application of an appropriate temperature in Example 1 when the capacity retention rate immediately after the cycle test in Comparative Example 1 described later is set to 100%. The excessive temperature was set in consideration of the degradation limit temperature of the solid-state battery.

[0054] Comparative Example 1 A solid-state battery was obtained in the same manner as in Example 1, except that a thermally expandable resin layer was not formed on the side surface of the laminate, and the laminate was inserted into a SUS case whose inside was insulated with tape so that the laminate would not come into contact with the SUS case. FIG. 5 is a schematic diagram of the solid-state battery of Comparative Example 1 (laminate-tape-SUS case). A durability test was performed on the solid-state battery of Comparative Example 1 in the same manner as in Example 1 to measure the capacity retention rate. Table 1 shows the results of the capacity retention rate after application of an excessive temperature in Comparative Example 1 when the capacity retention rate immediately after the cycle test in Comparative Example 1 is taken as 100%, and the capacity retention rate after application of an appropriate temperature in Comparative Example 1 when the capacity retention rate immediately after the cycle test in Comparative Example 1 is taken as 100%.

[0055] Comparative Example 2 A solid-state battery was obtained in the same manner as in Example 1, except that, as a two-layer resin coating, an epoxy resin was coated around the laminate and solidified to form a first thermal expansion resin layer on the side of the laminate, an acrylic resin was further coated around the laminate and solidified to form a second thermal expansion resin layer on the side of the first thermal expansion resin layer, and these were inserted into a SUS case. The total thickness of the first thermal expansion resin layer and the second thermal expansion resin layer was 4 mm, and a space was provided between the second thermal expansion resin layer and the SUS case so that the second thermal expansion resin layer would not come into contact with the SUS case. FIG. 6 is a schematic diagram of the solid-state battery of Comparative Example 2 (laminate-epoxy resin-acrylic resin-space-SUS case). A durability test was performed on the solid-state battery of Comparative Example 2 in the same manner as in Example 1 to measure the capacity retention rate. Table 1 shows the results of the capacity retention rate after application of an excessive temperature in Comparative Example 2 when the capacity retention rate immediately after the cycle test of Comparative Example 1 is taken as 100%, and the capacity retention rate after application of an appropriate temperature in Comparative Example 2 when the capacity retention rate immediately after the cycle test of Comparative Example 1 is taken as 100%.

[0056] [Table 1]

[0057] [Evaluation Results] It was confirmed that the solid-state battery of Example 1 had a higher capacity retention rate after application of an excessive temperature and a higher capacity retention rate after application of an appropriate temperature than the solid-state batteries of Comparative Examples 1 and 2. Therefore, it is found that the manufacturing method of the present disclosure can suppress the capacity decrease of a solid-state battery.

Claims

[Claim 1] A method for manufacturing a solid-state battery comprising: a laminate in which a positive electrode, a solid electrolyte layer, and a negative electrode are laminated in this order; a thermally expandable resin layer covering at least a portion of the laminate; and a metal case containing the laminate and the thermally expandable resin layer, Discharging the solid-state battery to 0% SOC; and applying a predetermined temperature to the discharged solid-state battery; The method for manufacturing a solid-state battery, wherein the thermally expandable resin layer and the metal case are in contact with each other.

Citation Information

Patent Citations

  • Method of inspecting all-solid battery

    JP2015122169A

  • Manufacturing method of all-solid lithium ion battery

    JP2018116812A

  • All-solid battery

    JP2019153535A

  • Manufacturing method for all-solid-state battery

    JP2020027742A

  • Manufacturing method of all-solid battery

    JP2020068170A